A new strategy in nursing education: From hybrid simulation to clinical practice. (April 2016) - Terzioğlu, Füsun; Yücel, Çiğdem; Koç, Gülten; Şimşek, Şahika; Yaşar, Beril Nisa; Şahan, Fatma Uslu; Akın, Rabiye; Öçal, Simge Evrenol; Akdağ, Cansu; Elçin, Melih; Mert, Merve; Yıldırım, Sevda
Summary: Background: Various instructional environments are used in nurse education to develop students' psychomotor and communication skills, reduce their anxiety levels, and enhance their satisfaction. Objectives: To examine the effect of three different instructional environments on the development of the students' psychomotor and communication skills and their levels of anxiety and satisfaction. Design: A prospective study design was used. Methods: The study sample consisted of 60 nursing students. Before the implementation of the study, the students' cognitive skills and trait anxiety levels were evaluated. The students were divided into five groups and five nursing activities (Leopold's maneuvers, teaching breastfeeding, family planning education, teaching vulvar self-examination and teaching breast self-examination) were specified for each group. They implemented these nursing activities under the supervision of a faculty member in the nursing skills laboratory (NSL), standardized patient laboratory (SPL) and clinical practice environment (CPE) respectively. In each instructional environment, the students' psychomotor and communication skills, state anxiety levels and satisfactions were evaluated. Results: The median scores for psychomotor skills [NSL = 73.1;SPL = 81.5;CPE = 88.6] and communication skills [NSL = 64.9;SPL = 71.6;CPE = 79.0] were found to increase as the students went on practicing in a more complicated environment ( p  < 0.05). Similarly, it was determined that the students' anxiety levels decreased as they were practicing incrementally [NSL = 33.0;SPL = 32.0;CPE = 31.0]. As the instructional environments were getting more similar to the reality, the students' satisfaction levels were found to become higher. Conclusions: Students who deliberately practice in the instructional environments until they are competent develop their psychomotor skills while reducing their anxiety levels, and enhancing their communication skills and satisfaction. For that reason, the development of students' competency areas is thought to be effective for enhancement of patients and health care workers' safety. Highlights: Using different instructional environments improves students' psychomotor skills. Using standardized patient improves students' communication skills. Repeating skill practices makes students' anxiety level lower. Students are more satisfied in instructional environments close to reality.